ANALISIS PENERAPAN PRINSIP PREJUDICIEL GESCHILL DALAM PUTUSAN SELA PENGADILAN NEGERI BEKASI NOMOR: 1242/Pid.B/2018/PN.Bks Tanggal 19 November 2018 - Nur Agustina Utami; Syarif Fadillah; F fauziah (Jurnal Hukum Jurisdictie, 2020)
The judge as the part that decides on the case plays a very important role in determining thefuture of the law, because each judge's decision will become the center of public attention. Thejudge does not only act as a mouthpiece of the law, but the judge also acts as the inventor of the law (recht vinding). The exercise of the authority of judges in criminal proceedings in law enforcement should uphold the principles that apply in the Criminal Procedure Code in court and benefit justice seekers. in the development of criminal procedure law in Indonesia,specifically regulating the postponement of criminal proceedings related to civil cases or socalled prejudiciel geschil in Indonesia, is regulated in Article 81 of the Criminal Code whichstipulates that "Postponement of criminal prosecution develops with judicial disputes, delaysexpired ". However, if examined closely, it seems that the provisions of Article 81 of theCriminal Code only link prayer disputes with expiration, but not explicitly which will takeprecedence when civil and criminal cases are brought to court at the same time. Theunregulated court dispute has clearly made the legal vacuum (rechtsvacuum) related toprejudicieel geschil, as well as lead to dualism in judicial practices in Indonesia.